Penjelasan BPOM RI Tentang Pemberitaan Hasil Pengawasan Produk Mie Instan Asal Indonesia di Taiwan dalam Perspektif Maqashid Syariah - Atun Nasikah, Rafi (Fakultas Syariah dan Ekonomi Islam, 2023)
In April 2023, the governments of Taiwan and Malaysia issued orders to recall one of the instant noodle products from Indonesia. Taiwan state health authorities stated that they had found the content of EtO which is commonly termed pesticide residue. Responding to this, BPOM Indonesia issued an official statement through an explanation on April 27, 2023, regarding the content of EtO, differences in regulations related to EtO to calls for being smart consumers. This article will discuss BPOM's explanation from the perspective of Maqashid Syari'ah